ADOLESCENT MENTAL HEALTH AND LIFESTYLE CHANGES: EXPLORING EATING DISORDERS AND PHYSICAL ACTIVITY DURING COVID-19 - Meilida, Anastasia; Hidayatunnufus, Inayah Aprilia; Helmyati, Siti; Latifah, Leny (Media Gizi Indonesia, 2025)
Background: Mental health, diet, and physical activity play an important role in adolescents development. However, previous studies have reported inconsistent findings on the relationship between mental health, eating disorders, and physical activity. The COVID-19 pandemic has negatively impacted mental health, potentially contributing to eating disorders and reducing physical activity. Objectives: This study aimed to examine the association between mental health, eating disorders, and physical activity in adolescents during the COVID-19 pandemic. Methods: A cross sectional quantitative study was conducted in 2022, involving 236 high school adolescents. Mental health was  assessed using the Depression, Anxiety, and Stress Scale (DASS-21), eating disorders were evaluate with the Eating Attitudes Test (EAT-26), and physical activity levels were measured using the International Physical Activity Questionnaire (IPAQ). Results: More than 50% of adolescents experienced depression, anxiety, or stress with severity ranging from mild to very severe. While 82.6% of adolescents did not exhibit eating disorders, 63.6% had low physical activity levels. A significant association was found between depression and eating disorders (p=0.024), but no significant relationship was observed between anxiety (p=0.080) or stress (p=0.232) and eating disorders. Additionally, depression (p=0.411), anxiety (p=0.547) and stress (p=0.097) were not significantly associated with physical activity. Conclusion: During the COVID-19 pandemic, most adolescents experinced mental health challenges, maintened normal eating behaviors, and exhibited low physical activity. Depression was significantly correlated with eating disorders, while no significant associations were found between mental health variables and physical activity levels.